PENGARUH SENAM YOGA TERHADAP PERUBAHAN TEKANAN DARAH PADA LANSIA YANG MENGALAMI HIPERTENSI DI KABUPATEN SIDOARJO - Erieska Safitri Hendarti; Ardiyanti Hidayah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2018)
Elderly is an age that is at high risk for degenerative diseases. One disease that is often experienced by the elderly is hypertension which can make the blood flow to be disrupted. One of the non-pharmacological treatments that can facilitate the flow of oxygen in the blood is yoga exercises. The purpose of this study was to analyze the effect of yoga exercises on changes in blood pressure in elderly people who have hypertension in Sidoarjo Regency. The design of the pre-experimental study used a pre-experimental one group pre test post test design design, independent variables: yoga exercise and dependent: changes in blood pressure in elderly people with hypertension carried out on July 4-27 2018 for 4 weeks with a frequency 1 time a week, 30 minutes of yoga exercises. The population used in this study were all elderly who experienced hypertension in Sidoarjo Regency, including 50 respondents selected according to inclusion criteria, using probability sampling sampling techniques with simple random sampling method. The measuring instrument used was observation, the results of which were analyzed by the Wilcoxon test. This study showed that there were changes in blood pressure after 4 weeks of yoga exercises, namely 42 respondents (84%) who experienced a decline and 8 respondents (16%) remained. So the results of this study indicate there is an effect of yoga exercises on changes in pressure. direction in elderly people who have hypertension in Sidoarjo Regency, with a value (p value = 0,000) <from a significant standard (α = 0.05). So there are differences in blood pressure measurement results before and after being given yoga exercises on changes in blood pressure in the elderly with a significant value.